2020
DOI: 10.1002/jgh3.12456
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and hepatic manifestations of COVID‐19: A systematic review and meta‐analysis

Abstract: performed data extraction and risk assessments. Michael K Dougherty performed data analysis and co-wrote the paper with Robert D Dorrell. Elizabeth T Jensen and Steven B Clayton provided oversight of the study. All authors contributed to the conceptualization of the study, interpretation of study results, and editing of manuscript drafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 57 publications
0
26
1
4
Order By: Relevance
“…Clinical presentation of COVID-19-positive subjects was in line with previous studies, with cough, fever, and loss of smell being the most commonly reported symptoms ( 2 ). Interestingly, we have shown that diarrhea was inversely correlated with disease risk, which was in disagreement with a recent systematic review that had suggested that gastrointestinal symptoms were experienced by 13% of all patients ( 17 ). Although the ROC estimates in this study seem rather high, new approaches predicting critical patients have managed to yield even greater estimates ( 18 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Clinical presentation of COVID-19-positive subjects was in line with previous studies, with cough, fever, and loss of smell being the most commonly reported symptoms ( 2 ). Interestingly, we have shown that diarrhea was inversely correlated with disease risk, which was in disagreement with a recent systematic review that had suggested that gastrointestinal symptoms were experienced by 13% of all patients ( 17 ). Although the ROC estimates in this study seem rather high, new approaches predicting critical patients have managed to yield even greater estimates ( 18 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, a recent study reported a significantly higher prevalence of GI manifestations in critically ill and hospitalized patients [ 24 ]. Another analysis by Dorrel et al reported a high prevalence of GI manifestations in severe COVID-19 patients [ 25 ]. A similar trend was noted in our study with more prevalence of GI manifestations in severe COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal symptoms are relatively common in human patients with COVID-19, and in approximately 2% of human cases, symptoms are restricted to the gastrointestinal tract. 25 Gastrointestinal symptoms can be the earliest or the primary manifestation of human disease. 21,22,[26][27][28] In humans, SARS-CoV-2 infection can cause gastrointestinal bleeding, ulceration, and ischemia from thromboembolism.…”
Section: Discussionmentioning
confidence: 99%